KONSEP MANAJEMEN KEUANGAN PRAKTIS DEMI PENINGKATAN KEMANDIRIAN UMKM Di KABUPATEN KUDUS - Darsin Darsin; Sukma Wijayanti; Nur Hayati (Universitas Muhammadiyah Semarang, 2025)
Empowerment of Micro, Small and Medium Enterprises (MSMEs) is currently showing a positive trend. This shows that MSMEs have a strategic position in national economic development, plays a role in development, employment and distribution of development results. This research focuses on increasing the financial independence of MSMEs through the application of financial management concepts that are practical and easy to understand. The research methods used include a survey of Kudus district MSME players, in-depth interviews with business owners, as well as analysis of available financial data. This research seeks to obtain the concept of practical financial management to increase independence for MSMEs in Kudus Regency by including determining samples using the purposive sampling method, collecting data and then testing it using PLS (Partial Least Square). The test results in the research show that practical financial management has a positive effect on independence. Kudus district MSMEs with a statistical t value of 4.722 and an original sample estimate value of 0.432 and financial management has a positive impact on Kudus district MSMEs with a statistical t value of 5.999 and an original sample estimate value of 0.550.